Kendala dan Strategi Implementasi Manajemen Risiko di Pemerintah Daerah Indonesia - Irianto, Gugus; Amirya, Mirna (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
Risk management in local governments in Indonesia is currently evolving as part of efforts to realize Good Governance. Risk management aims to minimize the likelihood and impact of risks that may hinder the achievement of organizational goals. This study aims to identify the challenges and strategies for implementing risk management in local governments in Indonesia based on a literature review. Using a literature study method and descriptive analysis, data were obtained from relevant articles and journals accessed through ScienceDirect and Google Scholar, both from national and international databases. The findings of this study reveal that the main challenges include a lack of understanding and awareness of risk management, resource limitations, regulatory misalignment, inadequate data, resistance to change, and lack of leadership support. The proposed strategies include training and education, adequate resource allocation, regulatory harmonization, data optimization, strengthening organizational culture, and increasing leadership commitment. The novelty of this study lies in the comprehensive analysis of the challenges and solutions in implementing risk management in local governments in Indonesia, an area that has not been deeply explored in previous studies.